Factors affecting users’ satisfaction towards smart system adoption among Inland Revenue Board (IRB) officers in Malaysia - Nur Farhana Hazwani, Abdul Basir (2022)
This paper examines the elements affecting on users’ satisfaction towards the adoption of Smart Management and Reliable Tax System (SMART) system among officers in Inland Revenue Board of Malaysia. SMART system was developed and implemented in 2019, which is based on Customer Relationship Management (CRM) method. CRM is one of the critical strategies that can be employed by public institution to have better deal with community request, improve overall public-government relationship, and also upgrade capability of government institution. Five critical elements are measured in this study by using the combination of Theory Planned Behaviour (TPB) and Technology Acceptance Model (TAM) which are; attitude, subjective norms, perceived behavioural control, perceived ease of use and perceived usefulness. The study was conducted in IRBM’s branches and departments throughout Malaysia involving 157 officers from the community of Customer Care Office. Multiple regression analysis is used to examine the relationship of the variables. The findings show that subjective norms, perceived ease of use and perceived usefulness are significantly related and contribute to users’ satisfaction towards the adoption of SMART system among IRBM’s officers.